Measurement of Foot Bone Mineral Density in Rheumatoid Arthritis: Its Application and Clinical Relevance - Kamanli, Ayhan; Suluhan, Ozlem; Ozgocmen, Salih; Kaya, Arzu; Ciftci, Ismail; Ardicoglu, Ozge (Turkish League Against Rheumatism, 2010)
Objective: Hand and foot joints are the primary targets in rheumatoid arthritis (RA) and decrease in the periarticular bone mineral density (BMD) is one of the earliest and considerable change in the affected joint. This study aimed to assess the relationship between foot bone mineral density (fBMD) measured by Dual Energy X-ray absorptiometry (DEXA) and BMD at axial sites, disease activity, functional status and quality of life in patients with RA Materials and Methods: 50 patients with RA, 40 age-and sex-matched patients with osteoarthritis (OA) and 14 voluntary healthy individuals were included in the study. C-reactive protein, erythrocyte sedimentation rate (ESR), Ritchie Articular Index (RAI), Health Assesment Questionnare (HAQ), and Foot Function Index (FFI) were measured. X-ray of the feet was scored by Larsen and Sharp/van der Heijde methods. Axial and fBMD were measured by DXA. Results: The results of the present study revealed that Turkish patients with RA carrying SE with HLA-DRB1 genes is significantly related with the production of anti-CCP. The diagnostic sensitivity and specificity of anti-CCP for RA is determined as 73,3% and 100% respectively. Conclusion: These results suggest for the first time that foot BMD measurement by DEXA is a useful and precise method. Foot BMD may reflect both localized and generalized bone loss and may be a potential outcome measure particularly in patients with marked foot involvement. (Turk J Rheumatol 2010; 25: 56-62)
Romatoid artritli hastalarda ayak kemik mineral yo?unlu?unun ölçülmesi: Yöntemin uygulanması ve klinik önemi
Keywords: Foot; bone mineral density; DEXA; rheumatoid arthritis